Contourner la coutume pour mieux disposer de ses biens à la fin du XIVe siècle en Normandie occidentale. À partir de quelques registres de tabellionage - Adrien Dubois; Christophe Maneuvrier (Tabularia)
A small corpus of unusual contracts found in various 14th-century notarial registers from western Normandy raises questions about the ability of Norman communities to circumvent customary rules, whether in order to be married, to establish common property, or to anticipate succession. Together, this prompts us to consider both the legal capacity of married women and the role played by 14th-century crises in these arrangements.